2019
DOI: 10.3791/59241
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral Vector Platform for the Efficient Delivery of Epigenome-editing Tools into Human Induced Pluripotent Stem Cell-derived Disease Models

Abstract: The use of hiPSC-derived cells represents a valuable approach to study human neurodegenerative diseases. Here, we describe an optimized protocol for the differentiation of hiPSCs derived from a patient with the triplication of the alpha-synuclein gene (SNCA) locus into Parkinson's disease (PD)-relevant dopaminergic neuronal populations. Accumulating evidence has shown that high levels of SNCA are causative for the development of PD. Recognizing the unmet need to establish novel therapeutic approaches for PD, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
0
12
0
1
Order By: Relevance
“…Functional titers will vary depending on the expression cassette packaged. It was found that using this protocol, the functional viral titer for Sp1-LVs carrying CRISPR/Cas9 transgenes was around 1 × 1,010 TU/mL per ∼5 × 10 7 producer cells ( Vijayraghavan and Kantor, 2017 ) and ( Tagliafierro et al., 2019 ).…”
Section: Expected Outcomesmentioning
confidence: 97%
“…Functional titers will vary depending on the expression cassette packaged. It was found that using this protocol, the functional viral titer for Sp1-LVs carrying CRISPR/Cas9 transgenes was around 1 × 1,010 TU/mL per ∼5 × 10 7 producer cells ( Vijayraghavan and Kantor, 2017 ) and ( Tagliafierro et al., 2019 ).…”
Section: Expected Outcomesmentioning
confidence: 97%
“…We demonstrated that cells targeted with LV-CRISPR/Cas9-DNMT3A showed substantial improvement in PD phenotypes, including nuclear transport, nuclear shape and integrity of the nuclear envelope, resistance to various stress stimuli, and others [ 65 ]. The optimized protocol for production of a lentivirus-CRISPR/dCas9 system at high-titers for transduction into primary cells, including hiPSCs and NPCs used in the above experiments, was published in [ 81 ]. The protocol describes how to produce, purify, and concentrate lentiviral vectors and to highlight their suitability for epigenome- and genome-editing applications.…”
Section: Lentiviral Vectors Paired With Genome-editing Toolsmentioning
confidence: 99%
“…A unique LV-based CRISPR/Cas9 system has recently been generated to simultaneously deliver the Cas9 nuclease and four different sgRNAs, each under the control of a different promoter, thus allowing the simultaneous editing of different cell types in targeted tissues (Kabadi et al, 2014 ). Additionally, an all-in-one LV carrying dCas9 fused with the catalytic domain of DNA-methyltransferase 3A (DNMT3A) has recently been tested to target SNCA triplication in hiPSC-derived dopaminergic neurons to efficiently reduce SNCA expression levels, rescuing mitochondrial ROS production and cellular viability (Kantor et al, 2018 ; Tagliafierro et al, 2019 ). Importantly, expression cassettes driven by astrocyte-specific [e.g., gfaABC(1)D and gfaABC(1)D(B3)] and oligodendrocyte-specific [e.g., myelin basic protein ( MBP ) and 2,3-cyclic nucleotide 3-phosphodiesterase ( CNP )] promoters readily fit within LV genome, favoring glia-specific expression of editing enzymes by using an “all-in-one” system (McIver et al, 2005 ; Kagiava et al, 2014 ; Merienne et al, 2017 ; Humbel et al, 2020 ).…”
Section: Viral Delivery Of Crispr/cas9 Systemsmentioning
confidence: 99%